OPTIMALISASI PENGELOLAAN LINGKUNGAN DENGAN PENDEKATAN HOLISTIK KULTURAL - Saipul Bahri; Taufan Ratri Harjanto; Rosita Dwityaningsih; Ayu Pramita; Nurlinda Ayu Triwuri; Sheptia Whiting Hayati (Journal of Science and Social Development, 2019)
The rapid population growth in Indonesia has an impact on increasing the amount of waste or household waste. Waste is the result of community activities so it should be instilled that waste management is a shared responsibility. According to the Central Statistics Agency of Indonesia, the amount of waste in 2020 in 384 cities in Indonesia will reach 80,235.87 tons every day. From the waste generated, it is estimated that 4.2% will be transported to the Final Disposal Site, 37.6% will be burned, disposed of into the river by 4.9% and untreated around 53.3%. One effort that has been made in Tambakreja Village, South Cilacap District, Cilacap Regency, Central Java through the use of household waste that is processed as compost to create a reduction in pollution to the environment. The waste or waste management program in Tambakreja Village RW 08 has been started since early 2014, namely processing waste in community settlements by launching a Waste Bank program called Bank Sampah Mandiri "Subur" (BSM Subur). However, because the program has just begun, the program has not gone according to plan. The low community participation in this program is one of the obstacles. In this village does not yet have a Final Shelter so that most of the population provides a monthly retribution fee for the collection of household waste that will be taken to the temporary disposal site. Waste originating from household activities is usually discharged directly without treatment, sometimes even waste from plantations and agriculture is directly burned in the yard. This is will cause negative impacts in the form of environmental pollution. This program is carried out to increase community participation in waste management by providing knowledge as well as assistance on the importance of holistic environmental management so that people can have the habit of reducing and anticipating environmental pollution that is around them. The results of this program showed that the community began to care about the garbage in their homes, care about their own health and the environment through community activities carried out continuously and began to be open in managing waste to prevent the burning of garbage in their environment.